1982
DOI: 10.1073/pnas.79.8.2722
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotential hemopoietic stem cells in adult mouse brain.

Abstract: Single cell suspensions ofadult mouse brain were shown to contain large numbers of pluripotential hemopoietic stem cells as detected by the ability to form hemopoietic colonies in the spleens of irradiated hosts. These colony forming unit, spleen (CFU-s) cells derived from brain gave rise to colonies identical in morphology and histology to those ofbone marrow-derived CFU-s. The average number of CFU-s obtained per 105 dissociated adult brain cells was 14, whereas other adult tissues such as lung, kidney, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Indeed, these cells cross an intact blood-brain barrier. Studies using chimaeric ani mals [21,22], immunological methods [23,24], and histochemical techniques [15,25,26] have allowed tracking of bone marrow derived mononuclear phagocytes to the brain where they become microglia. Such studies have added to phenotypic and functional evidence which would seem to substantiate del Rio H ortega's [27] origi nal proposal of mesodermal and not neuroectodermal origin of these cells [28],…”
Section: Microglia Are Bone Marrow-derived Brain Macrophagesmentioning
confidence: 99%
“…Indeed, these cells cross an intact blood-brain barrier. Studies using chimaeric ani mals [21,22], immunological methods [23,24], and histochemical techniques [15,25,26] have allowed tracking of bone marrow derived mononuclear phagocytes to the brain where they become microglia. Such studies have added to phenotypic and functional evidence which would seem to substantiate del Rio H ortega's [27] origi nal proposal of mesodermal and not neuroectodermal origin of these cells [28],…”
Section: Microglia Are Bone Marrow-derived Brain Macrophagesmentioning
confidence: 99%
“…Although it is a general concept that stem cells regenerate only a subset of differentiated cell types in a given tissue, the overall developmental potentials of a stem cell seem to be much wider than expected; different environmental cues determine different repertoires of potential stem cell fates. For example, muscle-derived cells can generate blood cells [7,8] and brain-derived cells can generate blood cells [9,10] or muscle [11,12].…”
mentioning
confidence: 99%
“…The confounding results of the following studies and the ensuing debate illustrate some of the problems facing the field of transdifferentiation and argues that in vitro cell culture could account for some of the observations. Several groups had reported that neural stem cells (NSCs) can differentiate into blood cells (Bartlett, 1982;Bjornson et al, 1999;Clarke et al, 2000;Shih et al, 2001). Bjornson et al (1999) reported that NSCs can differentiate into myeloid and lymphoid cells as well as early hematopoietic cells after injection of LacZ expressing NSC isolated from the brain or clonally derived NSC into sublethally irradiated mice resulted in LacZpositive hematopoetic cells in the BM as assessed by colony forming unit assays and by flow cytometry.…”
Section: Nuclear Reprogramming and Transdifferentiation: The Switch Bmentioning
confidence: 99%